THE EMPLOYMENT DISPUTE SETTLEMENT ACCORDING TO LAW NUMBER 43 OF 1999 ANALYZED FROM THE EMPLOYMENT AND ADMINISTRATIVE YUDICIAL SYSTEM - Lalu Ihsan (Fakultas Hukum Universitas Mataram, 2014)
This paper aims to look at the staffing dispute resolution pursuant to Act No. 43 of 1999 in terms of aspects of employment law and the system of Judicial Administration. Existence Personnel Advisory Board in the resolution of employment disputes, competency State Administrative Court and State Administrative High Court in the resolution of employment disputes and the status of the decision. Personnel Advisory Board and the position of the State Administrative Court judgment in the resolution of employment disputes. Normative legal research, analysis departs from the laws that describe the legal aspects related to the employment dispute resolution. Approach (statute approach), a conceptual approach (conceptual approach), approach the case (case approach). So that the position can be known BAPEK. Provide consideration to the president in the imposition of disciplinary punishment to the civil servants who are administratively BAPEK as body functioning decide administrative appeals filed by civil servants. Competence of the Administrative Court in the resolution of employment disputes, receive examine and decide disputes unrelated personnel by imposing rules violations Servants Discipline, and the dispute resolution employment appeal against the decision issued by the administrative court and BAPEK and Position decision BAPEK as Administrative Decision state that can be appealed to the judge’s decision Cosmos.Keywords: Resolution, Employment Disputes and Justice System Administrations.